2003
DOI: 10.1097/01.ju.0000052721.61645.a3
|View full text |Cite
|
Sign up to set email alerts
|

Extent of Pelvic Lymphadenectomy and Its Impact On Outcome in Patients Diagnosed With Bladder Cancer: Analysis of Data From the Surveillance, Epidemiology and End Results Program Data Base

Abstract: These results indicate significantly increased survival rates after cystectomy in patients with bladder cancer diagnosed with stages III or IV disease who have relatively more lymph nodes examined, suggesting that even some with higher stage disease may benefit from extended pelvic lymphadenectomy at cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
210
3
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(230 citation statements)
references
References 20 publications
9
210
3
8
Order By: Relevance
“…To further confound matters, the anatomic extent of node dissection and number of nodes retrieved varies widely between surgeons and institutions. Limited node dissections occur despite the well-documented potential for cure and evidence suggesting that complete node dissection may have a greater impact on survival than adjuvant chemotherapy [3]. In one prospective study, only the anatomic extent of node dissection (limited vs standard vs For reprint orders, please contact reprints@future-drugs.com extended) was associated with significant differences in nodal yield [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…To further confound matters, the anatomic extent of node dissection and number of nodes retrieved varies widely between surgeons and institutions. Limited node dissections occur despite the well-documented potential for cure and evidence suggesting that complete node dissection may have a greater impact on survival than adjuvant chemotherapy [3]. In one prospective study, only the anatomic extent of node dissection (limited vs standard vs For reprint orders, please contact reprints@future-drugs.com extended) was associated with significant differences in nodal yield [7].…”
mentioning
confidence: 99%
“…Since up to 25% of patients undergoing radical cystectomy have nodal metastases and 30% of patients with nodepositive disease may be cured by surgery, complete removal of disease burden requires a thorough nodal dissection [1,2]. Further support for a thorough node dissection at cystectomy is demonstrated by the fact that even N0 patients demonstrate improved survival if more (> nine in this reference) nodes are removed, presumably through the elimination of micrometastatic disease [3]. Surprisingly though, analysis of the Surveillance Epidemiology and End Results (SEER) registry revealed 40.3% of patients who undergo cystectomy do not undergo a lymph node dissection and, overall, 67.9% have fewer than six nodes removed [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Data from large ORC series have categorically shown that a good pelvic lymph node dissection is both diagnostic and improves overall survival [17][18][19]. The incidence of node positivity at the time of radical cystectomy exceeds 20%, and corresponds to increasing pathological stage, grade, and differentiation of bladder tumor.…”
Section: Lymph Node Dissection and Yieldmentioning
confidence: 99%